Sosialisasi Penerapan Halal pada Proses Produksi Es Batu Industri Rumah Tangga - Adhamatika, Adhima; Triardianto, Dimas; Kusumasari, Findi Citra; Indraloka, Aldy Bahaduri; Siska, Astri Iga (Insan Kreasi Media, 2024)
Indonesia is a country with a Muslim population of 207,176,162 people, or reaching 87.21% of the total population, so the need for halal products is quite high. This encourages business actors, especially in the food and beverage sector, to develop products based on halal guarantees. Where the aim is to guarantee the halalness of the products produced as regulated in Law No. 33 of 2014 concerning Halal Product Guarantees. One product that is widely used in the food and beverage industry today is ice cubes. Frozz Jaya Group Home Industry is an ice cube manufacturer that is preparing to apply for halal certification. This activity was carried out using learning service method. In this activity, 3 stages were carried out, namely socialization, observation and discussion to improve partners' preparation in applying for halal certification. This activity's results showed that several minor findings and positive things needed to be maintained. Partners are committed to immediately improving the conclusions of this activity so that they will be ready for halal certification. This was marked by several improvements such as applying for a well drilling permit and using tools and materials that are halal certified.